2018
DOI: 10.3390/nano8100819
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Gold Nanoparticles and Nanoclusters Composites with Enhanced Surface Raman Scattering and Metal Fluorescence for Cancer Imaging

Abstract: A large number of deaths from cancer can be attributed to the lack of effective early-stage diagnostic techniques. Thus, accurate and effective early diagnosis is a major research goal worldwide. With the unique phenomenon of localized surface plasmon resonance (LSPR), plasmonic nanomaterials have attracted considerable attention for applications in surface-enhanced Raman scattering (SERS) and metal-enhanced fluorescence (MEF). Both SERS and MEF are ultra-sensitive methods for the detection and identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Obviously, it is of the utmost importance to investigate the application of the codelivery system in diagnosis and therapy. Thereby, cRGD with high binding affinity to the α v β 3 integrin upregulated in tumor endothelial cells was conjugated onto the codelivery system to target hepatocellular carcinoma . We have characterized the physicochemical properties of a targeting codelivery system (IO–DB-cRGD).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, it is of the utmost importance to investigate the application of the codelivery system in diagnosis and therapy. Thereby, cRGD with high binding affinity to the α v β 3 integrin upregulated in tumor endothelial cells was conjugated onto the codelivery system to target hepatocellular carcinoma . We have characterized the physicochemical properties of a targeting codelivery system (IO–DB-cRGD).…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, cRGD with high binding affinity to the α v β 3 integrin upregulated in tumor endothelial cells was conjugated onto the codelivery system to target hepatocellular carcinoma. 46 We have characterized the physicochemical properties of a targeting codelivery system (IO−DB-cRGD). In Figure 3a− c, it was found that the hydrodynamic diameter of the IO−DB-cRGD was about 112.07 ± 1.27 nm, which was significantly larger than the 80 nm size in the TEM image (Figure 3a) due to hydrophilic interaction.…”
Section: Mechanism Of Strong Loading Capacitymentioning
confidence: 99%
“…Gold nanomaterials have attracted great interest for biological and chemical sensing applications due to their unique optical, chemical, electrical, and catalytic properties [63–64] . The absorption wavelengths of gold nanomaterials were considered to change with different morphologies of nanoparticles in the full spectral range due to the local surface plasmon resonance (LSPR) effects.…”
Section: Gold Nanomaterials For Sersmentioning
confidence: 99%
“…Gold nanomaterials have attracted great interest for biological and chemical sensing applications due to their unique optical, chemical, electrical, and catalytic properties. [63][64] The absorption wavelengths of gold nanomaterials were considered to change with different morphologies of nanoparticles in the full spectral range due to the local surface plasmon resonance (LSPR) effects. Besides, the LSPR also leads to a strong electric field on the surface of the gold nanostructure, which greatly enhances the optical signals that generated by molecules close to the surface (e. g., SERS).…”
Section: Gold Nanomaterials For Sersmentioning
confidence: 99%
“…Cancer has become one of the most serious causes of disease-related death, accounting for about 15% of total human deaths every year. [ 1 ] In Iran, cancer is the third major cause of mortality and disability[ 2 ] Chemotherapy is an important component of treatment for many cancers. [ 3 ] The administration of chemotherapeutic drugs may have numerous short-term and long-term side effects.…”
Section: Introductionmentioning
confidence: 99%